INDONESIA-AUSTRALIA ECONOMIC DIPLOMACY EFFORTS: CASE STUDY OF INDONESIA-AUSTRALIA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IA-CEPA) - Jenni Anthonetha Susanti Henukh; Triesanto Romulo Simanjuntak; Roberto Octavianus Cornelis Seba (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Indonesia-Australia Comprehensive Economic Partnership Agreement(IA-CEPA) is a strategic economic cooperation framework built by Indonesia and Australia with the aim of improving the economy and achieving the national interests of each country. This study aims to analyze how Indonesia-Australia's economic diplomacy efforts are through a case study of IA-CEPA. The research method used is a qualitative method with literature study and interview data collection techniques. The results of the study show that although Indonesia's trade balance still shows a deficit trend because the import value is greater, IA-CEPA is not fixated on the existing trade balance deficit. There are other sectors that help Indonesia achieve its national interests, for example through working holiday visas, Mutual Recognition Agreement (MRA), increasing foreign investment (FDI), improving workforce skills, and people-to-people connectivity. The results of the study also describe that Indonesia-Australia's economic diplomacy efforts did not stop during the negotiation period for cooperation, but also continued during the implementation period when the two countries had to coordinate and harmonize in facing and resolving the challenges of IA-CEPA. The economic diplomacy between the two countries that was established helped Indonesia and Australia to achieve their respective national interests, where state and non-state actors played crucial roles. This is in line with the theory of liberalism which views cooperation in international relations optimistically and makes it a place of interaction for state and non-state actors.